Doing PDS : stories and strategies from successful clinically rich practice - Garas-York, Keli; Hill, Pixita del Prado; Day, Leslie K.; Truesdell, Kim; Keller-Mathers, Susan (Research in professional development schools., 2018)
"SUNY Buffalo State is a unique urban comprehensive liberal arts public institution serving a large number of first generation college students. One flagship program at the college is the Professional Development Schools (PDS) consortium. Beginning in 1991 with one partner school, the SUNY Buffalo State PDS consortium now partners with approximately 45 schools locally, in Western New York, New York City, and across five continents. This book seeks to share the skills, knowledge, and examples of evidence-based practice of this innovative program to offer readers ideas for how teacher education and professional development might be re-conceptualized and re-energized. As many educators at all levels worry about external forces pushing the learning process toward greater standardization, the example of the SUNY Buffalo State PDS offers realistic and doable ways to meet the varying needs of educational communities through innovative practices that benefit all members of school partnerships - children, their families, practicing teachers, teacher candidates, administrators, and university faculty. While the PDS consortium aligns with the goals of the NCATE PDS Standards (2001), the NAPDS Nine Essentials (2008), and the NCATE Blue Ribbon Panel Report (2010) thereby providing an important structure to the large network, its design ensures flexibility and creative solutions to the real problems facing education. In an accessible and user-friendly way, the book includes specific examples to provide explanations and models, templates of tools we have successfully used, and resources to develop new programs or enhance existing ones"--